2016
DOI: 10.3389/fimmu.2016.00421
|View full text |Cite
|
Sign up to set email alerts
|

Increased TNF-α/IFN-γ/IL-2 and Decreased TNF-α/IFN-γ Production by Central Memory T Cells Are Associated with Protective Responses against Bovine Tuberculosis Following BCG Vaccination

Abstract: Central memory T cell (Tcm) and polyfunctional CD4 T cell responses contribute to vaccine-elicited protection with both human and bovine tuberculosis (TB); however, their combined role in protective immunity to TB is unclear. To address this question, we evaluated polyfunctional cytokine responses by CD4 T cell effector/memory populations from bacille Calmette–Guerin (BCG) vaccinated and non-vaccinated calves by flow cytometry prior to and after aerosol challenge with virulent Mycobacterium bovis. Polyfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 84 publications
(119 reference statements)
1
23
0
Order By: Relevance
“…IFN-γ secreting T CM cells are believed to play a major role in vaccine-induced protection in parasitic infections ( 44 ). Therefore, we measured the percentage of CD62L+ CCR7+ T CM cells that expressed intracellular IFN-γ.…”
Section: Resultsmentioning
confidence: 99%
“…IFN-γ secreting T CM cells are believed to play a major role in vaccine-induced protection in parasitic infections ( 44 ). Therefore, we measured the percentage of CD62L+ CCR7+ T CM cells that expressed intracellular IFN-γ.…”
Section: Resultsmentioning
confidence: 99%
“…Cattle that were first vaccinated with BCG and then infected with M . bovis had lower level of IFN-γ, TNF-α, and IL-2 than unvaccinated cattle [ 50 ]. However, in our study these changes in Th1 and Th2 cytokines are transient and may not be as effective markers for the assessment of confounding factors as the more stable trends in growth seen with Mtb CFUs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been demonstrated that BCG vaccinated cattle that were challenged by M . bovis produced expanded effector and central memory T cell populations [ 50 ]. A recent review identified both central and effector memory T cell populations as being key targets of activation in Mtb vaccine studies [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond IFN-γ-and/or IL-2-specific T cell responses, we used the statistically robust COMPASS analysis to probe polyfunctional T cell responses encompassing 8 effectors representing a total of 256 immune subsets (66). Polyfunctional Mtb-specific CD4 + T cells simultaneously expressing IFN-γ, IL-2, and TNF-α in blood are implicated in anti-TB immunity (67,68) and are shown to be critical in modulating vaccine-mediated immunity in murine rechallenge studies (69)(70)(71)(72). Further, we previously showed Mtb-specific polyfunctional cells expressing up to 4 cytokines to be associated with controlled latent infection (49).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%